Frequency and Causes of Methotrexate Intolerance and Discontinuation in Rheumatoid Arthritis Patients in Qena Governorate - Sondos Mohammed Sayed; Mohamed Ismail Abdelkareem; Eman Ragab Abdelradi; Wael Abd El-Mohsen Abady (SVU - International Journal of Medical Sciences)
Background: Methotrexate (MTX) is a conventional disease-modifying anti-rheumatic drug that has been used as first-line therapy for rheumatoid arthritis (RA), the frequency of MTX side effects and its discontinuation has been documented earlier, although it hasn't been fully investigated yet. Objectives: To evaluate the causes and frequency of methotrexate therapy discontinuation in rheumatoid arthritis patients in Qena governorate and to determine risk factors that may increase the incidence of MTX intolerance. Patients and methods: This hospital-based cross-sectional study was done on 200 patients with RA at the outpatient clinic of physical medicine, Rheumatology, and Rehabilitation Department of Qena University Hospital. All patients underwent a comprehensive history taking that included the reason for stopping methotrexate, a comprehensive clinical examination, a laboratory evaluation, and scoring of their disease activity. The patients were categorized into two groups based on their current MTX administration status. Results: A total number of 90 (45%) patients stopped using MTX within 3months to 26 years duration for various reasons; the most frequent reasons for stopping were gastrointestinal and hepatic adverse effects, representing together 55.5% of causes of discontinuation. The two groups had a significant statistical difference regarding corticosteroid intake and the current steroid dose. Conclusion: MTX appears to be a safe medication for RA patients to utilize for an extended period. To achieve the most benefit from an essential component of RA treatment, additional initiatives should be carried out to reduce the negative consequences and stoppage rate of methotrexate.